2006
DOI: 10.1017/s0003055406061995
|View full text |Cite
|
Sign up to set email alerts
|

“Plata o Plomo?”:Bribe and Punishment in a Theory of Political Influence

Abstract: W e present a model where groups attempt to influence policies using both bribes (plata, Spanish for silver) and the threat of punishment (plomo, Spanish for lead). We then use it to make predictions about the quality of a country's public officials and to understand the role of institutions granting politicians with immunity from legal prosecution. The use of punishment lowers the returns from public office and reduces the incentives of high-ability citizens to enter public life. Cheaper plomo and more resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(117 citation statements)
references
References 46 publications
5
107
0
5
Order By: Relevance
“…Dal B o et al (2006) show how credible threats from criminal organisations with a strong military power could lead to the adverse selection of politicians, as only those with worse external opportunities would run for appointment in mafia-ridden areas. Dal B o et al (2006) show how credible threats from criminal organisations with a strong military power could lead to the adverse selection of politicians, as only those with worse external opportunities would run for appointment in mafia-ridden areas.…”
Section: Lessons From Italian Mafias: a Previewmentioning
confidence: 99%
See 2 more Smart Citations
“…Dal B o et al (2006) show how credible threats from criminal organisations with a strong military power could lead to the adverse selection of politicians, as only those with worse external opportunities would run for appointment in mafia-ridden areas. Dal B o et al (2006) show how credible threats from criminal organisations with a strong military power could lead to the adverse selection of politicians, as only those with worse external opportunities would run for appointment in mafia-ridden areas.…”
Section: Lessons From Italian Mafias: a Previewmentioning
confidence: 99%
“…From a theoretical perspective, Dal B o and Di Tella (2003) and Dal B o et al (2006Dal B o et al ( , 2007 have shown that criminal groups with sufficient economic and military power may affect policies by either bribing or intimidating politicians in office (Kugler et al, 2005). From a theoretical perspective, Dal B o and Di Tella (2003) and Dal B o et al (2006Dal B o et al ( , 2007 have shown that criminal groups with sufficient economic and military power may affect policies by either bribing or intimidating politicians in office (Kugler et al, 2005).…”
Section: Organised Crime Corruption and Political Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with competition over market share, this rivalry may spark violence between organizations. 6 Still, if the state has the capacity to cut durable deals with the organizations, it can mitigate struggles over market share and thus potentially maintain peace. Conversely, in the "many protectors, one organization" scenario preferred by criminal organizations, violence may occur between protectors as they compete to control the income generated by a single organization.…”
Section: Protection In Time and Spacementioning
confidence: 99%
“…Dal Bó et al[6] use a similar logic to explain how pressure groups extract policies more easily from government officials when they can use both transfers, such as bribes, and threats at the same time in order to get policy favors.…”
mentioning
confidence: 99%